2021
DOI: 10.1002/cbf.3663
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis induction in breast cancer: A paracrine paradigm

Abstract: Breast cancer is the most prevalent type of cancer among women globally. Angiogenesis contributes significantly to breast cancer progression and dissemination. Neovascularization is concurrent with the progression and growth of breast cancer. Breast cancer cells control angiogenesis by secreting pro-angiogenic factors like fibroblast growth factor, vascular endothelial growth factor, interleukin, transforming growth factor-β, platelet-derived growth factor and several others. These pro-angiogenic factors trigg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 115 publications
0
16
0
Order By: Relevance
“…Cancer cells in uence angiogenesis by secreting various agents such as growth factors, integrin, interleukins as well as MMPs. Neovascularization promotes the progression and spread of breast cancer in return [22].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells in uence angiogenesis by secreting various agents such as growth factors, integrin, interleukins as well as MMPs. Neovascularization promotes the progression and spread of breast cancer in return [22].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, unlike normal vessels, tumor vessels are tortuous and chaotically organized, with wide gaps between endothelial cells, detached pericytes, and basal membranes that are either too thick or too thin [ 21 ]. All these features are typical of BC [ 31 ]. Importantly, BC biopsies are routinely evaluated for vessel density, which reliably predicts the risk of BC recurrence/metastasis and, thereby, BC patients’ survival rate [ 32 , 33 ].…”
Section: The Abnormal Tumor Vasculature Of Breast Cancermentioning
confidence: 99%
“…Dysregulated tumor-associated angiogenesis is orchestrated by a variety of molecular players, such as vascular endothelial growth factor (VEGF), interleukin 8 (IL-8), pleiotrophin, angiopoietin-1, angiopoietin-2, platelet-derived growth factor (PDGF), fibroblast growth factor (FGF)-2, and transforming growth factor beta-1 (TGFβ-1). Clinical studies have shown that elevated levels of these cytokines are associated with a worse prognosis of several tumor types [ 48 , 49 , 50 ] and also play a critical role in BC progression [ 31 , 51 ].…”
Section: The Abnormal Tumor Vasculature Of Breast Cancermentioning
confidence: 99%
“…Neovascularization in angiogenesis significantly contributes to BC progression and dissemination. BC cells are able to secrete pro-angiogenic factors, such as fibroblast growth factor (FGF), vascular endothelial growth factor (VEGF), interleukins (ILs), transforming growth factor beta (TGFβ), platelet-derived growth factor (PDGF), that control the angiogenesis and metastasis since they can trigger neovascularization [131].…”
Section: Anti-angiogenic Effectsmentioning
confidence: 99%